Hubungan Pengetahuan Ibu dan Peran Kader Terhadap Partisipasi Ibu Balita Dalam Kegiatan Posyandu Balita di Desa Lubuk Dendang Kec. Perbaungan Sergai Tahun 2022 - Dorito Maryani Harahap; Zulkarnain Batubara; Rosmega Rosmega (Pusat Riset dan Inovasi Nasional, 2024)
Posyandu is one form of health efforts resourceful community which is a real form of community participation in health development. Two factors that affect children visit that factor maternal knowledge of ignorance weigh the benefits against her mother in IHC. And the role of the factor Kader duty to urge people who have or which includes the target of immunization to Posyandu and provide peyuluhan the research aims to determine the relationship of mother's knowledge and the role of cadres to visit diposyandu toddler. Study Design This study is analytic with cross sectional approach. Sample of 35 respondents conducted in the mother at Lubuk dendang village Perbaungan district Serdang bedagai in 2022. Data was collected by distributing questionnaires. Result (73.0).of the relationship with the mother's knowledge toddler visit diposyandu find p = 0.017 and cadres role relationships with toddlers visit diposyandu find p = 0.025. Conclusion There is a significant association between mother's knowledge and the role of cadres to visit health centers toddler at Lubuk dendang village Perbaungan district. The need for care advice from health workers about health education to the community, especially pregnant women and mothers with young children about the importance of a visit to Posyandu. For relevant institutions in this case the clinic in order to pay attention to cadre's refreshment in order to keep motivated in carrying out its function and role in Posyandu.